Effect of Cryopreservation on Viability, Immunophenotype and Differentiation Properties of Mesenchymal Stromal Cells of Early Organogenetic Stage - Trufanova, N. A.; Petrenko, Yu. A.; Petrenko, A. Yu. (Problems of Cryobiology and Cryomedicine, 2010)
The effect of cryopreservation by slow program cooling on the viability, immunophenotypic and differentiative properties of mesenchymal stromal cells (MSCs) of early organogenesis stage was studied. It was shown that after cryopreservation under the protection of 10% dimethyl sulfoxide (Me2SO) at the cooling rate of 1°C/min down to –80°C with the following plunging into liquid nitrogen the cell viability assessed by trypan blue staining was 88.4 ± 1.7%. The metabolic activity of cells assessed by Alamar Blue reduction assay decreased after cryopreservation by 15%. Immunophenotypic analysis of MSCs after 4–12 passages showed that 95% of cells expressed the markers CD29, CD44, CD73, CD105 prior to and after cryopreservation. The number of CD34–, CD38– and CD45– cells was more than 95%. After cryopreservation MSCs maintained their capacity for induced differentiation into osteogenic and adipogenic directions. Slow cooling with Me2SO as cryoprotectant was observed to stimulate differentiation of MSCs.